Thematic evolution of scientific publications in spanish - Bianco, Santiago
Thematic evolution is a relevant technique when processing text documents about a specific topic but from different periods of time. Identifying changes in terminology and the evolution of research fields is of great interest to disciplines such as bibliometrics and scientometrics. In this article, strategies are proposed to improve the analysis of thematic evolution in scientific publications in Spanish, together with visualization techniques that allow highlighting the most relevant results. In principle, this methodology can be used in different contexts; however, here we apply it to the analysis of the scientific production related to technology in education and technology education, as an expansion of the work carried out in [1]. The tests implemented allow us stating that the inclusion index is an adequate metric to select the most relevant topic relationships, facilitating the understanding and visualization of the results obtained.